(untitled) (Al-Academy, 2025)
Lighting is an important and effective element in architecture, and the reason for the individual’s interaction with space and mass. Lighting design is a mixture of science and art. It is a design, creative and artistic process to highlight the aesthetic and functional values in architecture. Color plays a decisive elemental role in interior architecture. The choice of colors can greatly affect the overall design. One of the main reasons why color is essential in architecture is its ability to influence the psychology of individuals. The aim of the research was to know the psychological effects of lighting and colors and to study their effect in highlighting the functional and aesthetic values of the interior spaces in the home, in addition to reaching the differences between the sample items according to the demographic variables and finding the relationships between them. The most important results reached by the researcher were: 1- There is a statistical difference between the averages of the sample individuals in the effect of the lighting and color elements in highlighting the functional and aesthetic values of the interior spaces of the residence. 2- There is a positive direct correlation between the effect of the lighting and color elements in highlighting the functional and aesthetic values of the interior spaces of the residence and the demographic variables. 3- The difference in the percentage of participation of the factors affecting the highlighting of values. The researcher recommended a set of recommendations: 1- Holding training courses and programs for female students and graduates to train them on how to achieve a balance between lighting and color to increase their positive impact on the interior designs of buildings according to different spaces. 2- The necessity of achieving home sustainability standards by making maximum use of interior spaces through distributing different lighting. 3- Community service units cooperate with specialized colleges to hold advisory meetings for various segments of society to increase their awareness in a scientific manner regarding the effect of lighting and color on the interior spaces of buildings.